Impact of Egg Storage Duration and Temperature on Egg Quality, Fertility, Hatchability and Chick Quality in Naked Neck Chickens - Addo, Alex; Hamidu , Jacob Alhassan; Ansah, Addo Yaw; Adomako, Kwaku (International Journal of Poultry Science, 2018)
Background and Objective: It is well a known fact that storing hatching eggs over a longer period of time affects egg quality, fertility and hatchability. The current study evaluated the impact of five egg storage durations and two temperature conditions on egg quality, fertility, hatchability and chick quality in a 6th generation heterozygous naked neck chickens. Methodology: A total of 900 hatching eggs were initially obtained from 45 weeks old flocks in five batches and weighed. Eggs (n=180) were obtained each time and divided into 2 groups. Each group was stored at one of two egg storage temperature conditions: cold room temperature (18°C) or ambient temperature (25-30°C). In each temperature condition the eggs were subjected to five pre-incubation egg storage duration of 1, 3, 7, 10 and 14 days. Thus, the experimental design used was a 2×5 factorial design consisting of two temperature conditions (cold room and ambient) and 5 pre-incubation egg storage durations (1, 3, 7, 10 and 14 days). After storage 15 eggs per treatment were weighed and broken to determine egg quality parameters including blastoderm diameter, eggshell, yolk and albumen weights. The remaining eggs were incubated for 21 days at 37.5°C and 60% relative humidity. The parameters measured were fertility, total hatchability, embryonic mortality and chick quality. The fertility, hatchability and embryo mortality were expressed as percentages. Data were analyzed using the Proc. mixed Model procedure of SAS at p<0.05. Results: The results showed no impact of experimental treatments on initial egg weight before and after eggs storage. However, the blastoderm quality reduced as the egg storage duration increased. Storing eggs in ambient temperature compared to cold room temperature resulted in increased blastoderm diameter and advanced embryo development. This resulted in higher embryo mortality during incubation, lowered fertility and reduced hatchability. The albumen weight and dry yolk weight significantly reduced after longer storage. Chick weight and chick shank length were increased in eggs stored at cold room temperature compared to eggs stored at ambient temperature but reduced as storage duration increased. Conclusion: Improperly storing eggs can greatly reduce fertility, hatchability and chick quality as a result of poor embryogenesis and overall chick development.